Analysis of The Impact of Internal Control Systems, Accounting Information Systems, and Human Resources on Financial Reporting With Organizational Commitment As a Moderating Variable (Case Study of Asyratun Cooperative, Muhammadiyah Vocational School 10 K - Reza Safrianto; Dito Aditia Darma Nst; Agus Tripriyono (Jurnal Multidisiplin Indonesia, 2026)
This study aims to analyze the influence of Internal Control System, Accounting Information System, and Human Resources on Financial Statements and examine the role of Organizational Commitment as a moderation variable in the Asyratun Cooperative of SMK Muhammadiyah 10 Kisaran. The background of this research is the lack of optimal internal control, inaccuracy of transaction recording, and low competence of the management in preparing financial statements. The study used a quantitative method with a saturated sampling technique involving all 50 cooperative members as respondents. Data were collected through questionnaires and analyzed using validity, reliability, classical assumption tests, and multiple linear regression. The results of the study show that the Internal Control System, Accounting Information System, and Human Resources have a positive and significant effect on the Financial Statements, both partially and simultaneously. In addition, the Organizational Commitment has been proven to moderate the influence of independent variables on the Financial Statements by strengthening the relationship. These findings confirm that the quality of cooperative financial statements is highly determined by the effectiveness of internal controls, the reliability of accounting information systems, the competence of human resources, and the organization's commitment to supporting financial operations and accountability.